TINJAUANYURIDIS MEKANISME PENDAFTARAN CALON PERSEORANGAN DAN PARPOL DALAM PILWALI DI KOTA KEDIRI - Agus Manfaluthi (UNIVERSITAS ISLAM KADIRI, 2015)
Objective research titled Judicial Review of Registration Mechanism for Independent Candidates and Political Parties in the General Election of Mayor and Deputy Mayor (Pilwali) in 2013 to determine the depth of the registration mechanism for independent candidates and political parties in the general election of Mayor and Deputy Mayor in Kediri. The question is whether Kediri has been carrying out the registration procedure in accordance with the rules applicable. To mind the new independent candidates Pilwali adopted in 2013 in Kediri where it is the first time to implement Election Mayor followed by independent candidates. This research is conducted using empirical methods to the scope of research locations in the Election Commission office Kediri. The result: Based on Law Number 12 Year 2008 began chapters 58 to 60, the General Election Commission (KPU), Kediri City has been implementing a mechanism for registration of candidates for May or and Deputy Mayor came from political parties, the combined political parties and candidates Individual earnest, result all independent either from independent or from political party and coalition of political parties passed the registration stage